KARAKTERISTIK FISIK KUALITAS BIJI KOPI DAN KUALITAS KOPI BUBUK SINTARO 2 DAN SINTARO 3 DENGAN BERBAGAI TINGKAT SANGRAI - Budiyanto Budiyanto; Damres Uker; Toto Izahar (BPFP Faperta UNIB, 2021)
Juremian and Kirmanan are other names for the Sintaro 2 and Sintaro 3 coffee clones, the national superior robusta coffee clones that have been cultivated in Sidorejo Village. This study aims to determine the quality and physical properties of coffee beans, chemical properties and ground coffee quality of Juremian and Kirmanan clones. The quality and physical properties of coffee beans are evaluated according to the Indonesian National Standard (SNI) 01-02907-2008 procedure. The chemical properties and quality of ground coffee powder were evaluated based on SNI 01-3542-204 procedure as well as the cupping test method (Specialty Coffee Association of America). The results showed that Juremian coffee beans had fewer defects and bean sizes, more peaberry beans, and better bean quality than Kirmanan coffee beans. Based on coffee extract content,